2021
DOI: 10.1108/jm2-02-2021-0038
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of belt and road infrastructure projects using integrated ISM-MICMAC approach

Abstract: Purpose The historic Belt and Road Initiative (BRI) is an economic reform policy proposed by the Chinese Government that focuses on connectivity, improved collaboration and more robust economic relations. This paper aims to identify risks involved in BRI infrastructure project and establish a hierarchical relationship among them. Design/methodology/approach The methodology includes two phases, namely, identification of significant risks involved in the BRI project using systematic literature review and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…, 2019). For example, Nikjow et al. (2021) integrated ISM–MICMAC approach to construct the hierarchical relationship between the significant risks of the Belt and Road Initiative infrastructure projects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2019). For example, Nikjow et al. (2021) integrated ISM–MICMAC approach to construct the hierarchical relationship between the significant risks of the Belt and Road Initiative infrastructure projects.…”
Section: Methodsmentioning
confidence: 99%
“…However, to focus on more effective mitigation strategies, MICMAC analysis is complementary to the ISM method, assisting to understand and discuss key factors in complex system (Troche-Escobar et al, 2018;Ma et al, 2019). For example, Nikjow et al (2021) integrated ISM-MICMAC approach to construct the hierarchical relationship between the significant risks of the Belt and Road Initiative infrastructure projects. They found that the economic risk, environmental risk and political risk in the ISM model have strong driving power, and should thus be taken into consideration when selecting risk mitigation strategies.…”
Section: Integrated Ism-micmac Approachmentioning
confidence: 99%
“…Source: Computation by authors JM2 19,4 Mani et al, 2016;Nikjow et al, 2021;Patri and Suresh, 2017). The total number of "1"s in the table's rows and columns were added, representing CSF's driving power and dependency for SCFE.…”
Section: Final Reachability Matrixmentioning
confidence: 99%
“…The BRI contributes to the advancement and expansion of the Silk Road Economic Belt and the 21st Century Maritime Silk Road and thus prolong the practice of wide-ranging opening of new segment of markets to represent the beginning of a new paradigm [1]. BRI infrastructure projects overseas have been a pathway to create strategic interconnectivity between China and other countries, further strengthening interdependence between China and the BRI partner countries [1,2]. Liu and Dunford [3] demonstrate developing particular infrastructure systems and new multilateral funding structures to support poverty mitigation and sustainable growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited research has identified and prioritized the triggers of delays in international EPC projects, especially HSR delay factors. Hence, the aim of this study is (1) to identify and categorize critical triggers of delay in the EPC HSR project from engineering, procurement, and construction phases; (2) to investigate the current state of management international EPC HSR construction projects among Chinese companies; and (3) calculate the relative significance triggers of delays and illustrate the rating of variables and related groups in terms of their importance concerning delays.…”
Section: Introductionmentioning
confidence: 99%